Spatial and temporal occurrence of forensically important South African blowflies (Diptera: Calliphorida) - Williams, Kirstin Alexa (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2003)
Forensic entomology is an emergjng field in South Africa. Little is known about South African blowflies and factors that affect their use in a forensic context. This work provides a review and synthesis of previous work in South Africa and supplements some of the background and basic knowledge required for forensic entomology in South Africa. The seasonal occurrence of eight forensicaIIy important blowfly species was quantified by fortnightly trapping in Grahamstown, South Africa. The spatial distribution of each species was related to seasonal occurrence and habitat preference. Seasonal distributions of blowflies in carcasses in South Africa were obtained from the literature and compared to the seasonal trapping. By mapping South African locality records of forensicaIIy important blowflies and analyzing these records in a modified Principal Components Analysis of climatic data, the potential geographic distributions of each fly species was modeIIed. Most species were widespread, but Calliphora croceipalpis, Jaennicke, 1867, was found in cold places. This information is important for determining where certain species are likely to occur in forensic investigations. Nocturnal oviposition was examined in both field and laboratory experiments. Lucilia species could oviposit nocturnaIIy in the field, while Lucilia species, Chrysomya chloropyga, (Weidemann, 1818) and C. putoria (Weidemann, 1830) could oviposit nocturnaIIy in the laboratory. These findings are important factors in affecting the precision of estimates of a post mortem interval (PM!) by up to 12 hours. The thermophysiological ranges of four species of adult blowflies were determined by measuring onset temperatures of four significant behaviours: onset of neural activity; onset of coordinated movement; shade-seeking and death. There was a sexual size dimorphism in Lucilia species, Chrysomya chloropyga and Calliphora croceipalpis with females being larger than males. Chrysomya megacephala (Fabricius, 1794) had an unexpectedly high death threshold, while Calliphora croceipalpis had the lowest death threshold of the flies tested. These points were related to the seasonal and geographic occurrence of each species, to nocturnal activity and placed in a forensic context.
Keywords: Blowflies -- South Africa; Forensic entomology